Bioindicadores para determinação de metais pesados no Reservatório da Itaipu Binacional, Paraná, Brasil - Chambo, Ana Paula Sartório (2011)
This study was conducted in the reservoir of Itaipu Hydroelectric Plant, located in the western region of Paraná State, during the March/2010 to April/2009 and aimed to study the chemical composition (macronutrients, micronutrients and toxic heavy metals), the bioaccumulation of biologically essential metals, copper (Cu), iron (Fe), zinc (Zn) and manganese (Mn), and non-essential toxic heavy metals, cadmium (Cd), chromium (Cr) and lead (Pb) in tissues of the armado (P. granulosus), mollusks (L. fortunei) and aquatic plants (E. densa and E. crasssipes), beyond the study of water quality and sediment under modified atmospheres, such as reservoirs for multiple uses, during the season the year. Fifteen fish were collected monthly to determine the factor relative corporal condition (Kn), the index of viscera total (IVT), visceral fat index (IGV), the hepatosomatic index (HSI) and the metal pollution index (MPI), as well as samples the sediment, water and the biomarkers golden mussel and two species of aquatic macrophytes, E. crassipes and E. dense. It was observed that the carcass of the armado bioaccumulate in the following order Fe, Ca, Zn, Pb, Mn, K, Mg, Cr, Cu e Cd. The nitrogen was concentrated in greater proportion in the carcass (110.58 g kg-1) and fillet (109.96 g kg-1) and phosphorus in the liver (43.26 g kg-1). The Cd was present in 50% of carcass samples (1.20 mg kg-1) and skin (1.00 mg kg-1) and 100% of the samples of gills (1.00 mg kg-1). The Cr was detected in 33% of carcass samples (2.75 mg kg-1) and gills (1.00 mg kg-1) and 17% of fillet samples (2.00 mg kg-1). The presence of lead was found in 100% of samples with levels ranging from 20.17 mg kg-1 in the carcass and 7.83 mg kg-1 in the fillet. The distribution of Cu, Zn and Mn in the sediment and water did not change seasonally. The analytical method used did not detect the presence of Cu and Zn in the water sample. The physical and chemical variables of water were not oscillated along the year season. The index calculated for the E. densa responded significantly seasonal fluctuations, with the highest rates were obtained during the summer followed by spring, winter and autumn. The armado captured during the experiment were contaminated by heavy metals Cd, Cr and Pb at levels above those recommended by current legislation. The rate of metal contamination suggests that the liver is the organ most bioaccumulate heavy metals in the gun. The deposition of heavy metals in sediment and water did not change seasonally, the sampling of sediment, E. densa and root of E. crassipes may indicate the composition of environmental contamination